TEACHING-21ST CENTURY LEARNING-MEDIA INNOVATION FOR EFL TEACHING AND LEARNING: PRE-SERVICE TEACHERS PERSPECTIVE - Asmi Rusmanayanti; Nasrullah (Getsempena English Education Journal, 2020)
Nowadays, EFL teachers are benefited by the abundance of technological resources that enable them to provide learners with sufficient comprehensible input. Yet, not all of them are literate to the available supported devices neither in the form of webs nor other internet applications. Therefore, this study aims at describing a view toward a trend of ICT use as learning resources both in a form of web and internet based applications used by pre-service teachers.This research employed mix-method research by using an open-ended questionnaire and interview with 24 pre-service teachers as participants who study in English department, Lambung Mangkurat University. The finding of this study revealed that even there are several pre-service teachers who encountered problems when using the available applications, nevertheless, most of them have a positive perspective on ICT use in teaching and learning activities. Moreover, it is found that mostly MALL (Mobile Assisted Language Learning) applications have familiar to be used during the learning time especially out of the class rather than CALL applications.